PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. AMIGDALA KARYA PEDIA MOJOKERTO - Muhammad Syamsudin Al Ghifari; Mahfudiyanto (CV. ALIM'SPUBLISHING, 2023)
This study aims to determine the effect of work motivation and work environment on the work productivity of employees of PT. Amygdala by Pedia Mojokerto. The method used in this study is quantitative research. The population in this study amounted to 40 respondents, with a sampling technique using a saturated sample that used all production employees as samples. The results of the study show that: (1) Motivation has a effect on the work productivity of PT. Amigdala Karya Pedia Mojokerto; (2) The work environment has a effect on the work productivity of employees of PT. Amigdala Karya Pedia Mojokerto; and (3) Work motivation and work environment have a effect on the work productivity of employees of PT. Amygdala by Pedia Mojokerto.